Application of MXene in Electrochemical Sensors: A Review - Wu, Xinzhao; Ma, Pinyi; Sun, Ying; Du, Fangxin; Song, Daqian; Xu, Guobao (Electroanalysis (New York, N.Y.), 2021)
Electroanalysis has obtained considerable progress over the past few years, especially in the field of electrochemical sensors. Broadly speaking, electrochemical sensors include not only conventional electrochemical biosensors or non‐biosensors, but also emerging electrochemiluminescence (ECL) sensors and photoelectrochemical (PEC) sensors which are both combined with optical methods. In addition, various electrochemical sensing devices have been developed for practical purposes, such as multiplexed simultaneous detection of disease‐related biomarkers and non‐invasive body fluid monitoring. For the further performance improvement of electrochemical sensors, material is crucial. Recent years, a kind of two‐dimensional (2D) nanomaterial MXene containing transition metal carbides, nitrides and carbonitrides, with unique structural, mechanical, electronic, optical, and thermal properties, have attracted a lot of attention form analytical chemists, and widely applied in electrochemical sensors. Here, we reviewed electrochemical sensors based on MXene from Nov. 2014 (when the first work about electrochemical sensor based on MXene published) to Mar. 2021, dividing them into different types as electrochemical biosensors, electrochemical non‐biosensors, electrochemiluminescence sensors, photoelectrochemical sensors and flexible sensors. We believe this review will be of help to those who want to design or develop electrochemical sensors based on MXene, hoping new inspirations could be sparked.